Perceived domains that could improve helmet wearing behaviour in two-wheeler riders: a cross sectional study among internet users residing in Tamil Nadu - T., Rangapriya A.; V., Ambayiram A.; R., Muruganandham (International Journal Of Community Medicine And Public Health, 2022)
Background: Road traffic accidents are major cause of morbidity and mortality. Correct helmet use can reduce fatal injuries of head and neck and death. The purpose of the study is to assess the knowledge, attitude and practice towards helmet wearing and to assess the barriers and facilitators of helmet wearing practice among internet users. Methods: An observational cross-sectional study was carried out among Internet users who rode motorcycle between August 1, 2020 to October 1, 2020. A pretested semi-structured online questionnaire was used to collect data for the study. The collected data was entered into Microsoft Excel Version 2019 and was analysed using SPSS version 26. Results: 29.9% had poor knowledge regarding helmets followed by 64.5% with moderate knowledge. 5.6% had good knowledge. With regard to attitude, only 5.5% had poor attitude while 66.4% and 27.9% had moderate and good attitude, respectively. Domains perceived by the participants influencing the helmet wearing behaviour included comfort (52.2%), legislative measures (38.5%), awareness (34.4%), design and quality of helmet (27.4%), cosmetic disadvantage (17.1%) and infrastructure (16.7%). Conclusions: Improving the knowledge and attitude among the participants would aid in promoting helmet wearing behaviour. Improving the comfortability while wearing helmet, more strict enforcement of laws for helmet wearing along with increasing the severity of them and increasing awareness through various means were the three most listed domains that could improve helmet wearing among two-wheeler riders.